GreenCycle: Ubah Limbah Dapur Jadi Pupuk Organik Cair di Desa Tegalweru - Muhammad Rifa'i; Muhammad Rakha Mahaputra; Marcelina Kusumaningtyas Ari Widyastuti; Bintang Alif Ramadhan; Yuliada Pawestri; Shintya Dita Afrina; Frannanda Raydhika Lyfanni; Janu Narendra; Angelica Wijaya; Febrianto Anung Anindito (PT. Hasba Edukasi Mandiri, 2026)
Household waste, particularly organic kitchen waste, frequently poses environmental challenges if not managed properly, as observed in Tegalweru Village. The